Disinfection by sodium hypochlorite dialysis applications - Ronco, Claudio 1951-; Mishkin, Gary J. (Karger, 2007)
Sodium hypochlorite has long been recognized for its effectiveness as an antiseptic and disinfectant, but its practical use in medicine had been limited due to its reduced stability. However, it has been shown that the method of manufacture can make the vital difference: The ExSept solutions (Amuchina) discussed in this publication differ from other commercially manufactured solutions insofar as they are produced with the help of electrolysis, the result being a highly effective antimicrobial with very good biocompatibility. The papers in this volume concentrate on the experiences made with ExSept solutions in dialysis applications. They provide a sound understanding of how electrolytically produced sodium hypochlorite solutions differ from other commercial solutions, present different uses as both an antiseptic and disinfectant and alleviate some of the stereotypes associated with their medical use. Both in vitro controlled laboratory evaluations and clinical in vivo prospective randomized trials are introduced in this publication, making it a valuable help for clinicians working in the field of dialysis
Introducing a new generation of sodium hypochlorite solutions
Includes bibliographical references and index
Keywords: Nephrology; Microbiology; Clinical Chemistry; Dialysis; Toxicology; Desinfektionsmittel; Kochsalz; Dialyse